Polysaccharide Based Formulations for Mucosal Drug Delivery: A Review - Boateng, Joshua; Okeke, Obinna; Khan, Sajjad (Current Pharmaceutical Design, 2015)
There has been increased interest in novel drug delivery systems to be administered via mucosal routes as an alternative to the currently used traditional routes such as parenteral (injections) and oral routes of administration. This is due to the several advantages they offer including avoiding first pass metabolism in the liver for oral administration and local activity which avoids the need for high systemic doses. To achieve the foregoing objectives, bioadhesive vehicles are required that ensure prolonged residence time to achieve systemic bioavailability via substantial drug absorption or significant drug concentration for local action. The drug delivery system is also required to be non-deleterious to the site of application and be well tolerated by vulnerable groups such as paediatric and geriatric patients. These essential characteristics are mainly satisfied by naturally occurring polymers, including polysaccharide based polymers which have the advantage of biocompatibility, biodegradability and therefore safety. This review discusses various bioadhesive polymers of polysaccharide origin formulated into a variety of dosage forms for drug delivery via the body’s mucosal (moist) surfaces including ocular, oral (buccal and sublingual), nasal, gastrointestinal and vaginal mucosa, as well as moist wound sites. The anatomy and / or physiology of each site, coupled with the unique challenges each poses, the strategies employed for ensuring therapeutic efficacy, as well as the current state of the art will also be covered.
Keywords: mucosal delivery